1991
DOI: 10.1002/pros.2990190405
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic effects of insulin and insulin‐like growth factors on PA‐III rat prostate adenocarcinoma cells: Characterization of the receptors involved

Abstract: Four transplantable cell lines (PA-I, II, III, and IV) derived from four Lobund-Wistar (L-W) rats that manifested spontaneous prostate cancer have demonstrated metastatic capacity in visceral organs. Interestingly, PA-III cells, when deposited over the scapula or calvarium of the Lobund-Wistar rat, could produce lytic and blastic reactions on rat skeleton. Since growth factors and growth factor receptors have been implicated in bone remodeling, cancer biology, and metastatic growth of cancer cells, we have exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
4

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 30 publications
2
42
0
4
Order By: Relevance
“…However, to our knowledge no one has demonstrated a direct effect of insulin on normal prostate tissue. A previous study from our laboratory 18 reported that insulin does stimulate the growth of the human LNCaP PCa cell line, and Polychronakos et al 19 reported that insulin stimulated the growth of rat PA-III adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 94%
“…However, to our knowledge no one has demonstrated a direct effect of insulin on normal prostate tissue. A previous study from our laboratory 18 reported that insulin does stimulate the growth of the human LNCaP PCa cell line, and Polychronakos et al 19 reported that insulin stimulated the growth of rat PA-III adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 94%
“…Circulating insulin levels increase linearly with increasing obesity, and insulin has been implicated in prostate cancer biology (50), with higher risk of prostate cancer (51), and with higher recurrence of the disease (52). Circulating concentrations of total IGF-I have been associated with higher risk of prostate cancer (53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated epithelial cells of rat ventral prostate have insulin receptors, and fasting increases their concentration (Carmena et al, 1986). But PA-III rat prostate adenocarcinoma cells have no insulin receptor, though they do have specific binding sites for IGF-I and II (Polychronakos et al, 1991).…”
Section: Discussionmentioning
confidence: 99%